2011
DOI: 10.1016/j.cveq.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Insufficiency in Horses and Foals

Abstract: SYNOPSIS The adrenal cortices produce a variety of steroid hormones (corticosteroids) that play vital roles in a number of physiologic processes, including: electrolyte and fluid balance; cardiovascular homeostasis; carbohydrate, protein and lipid metabolism; immune and inflammatory responses; and sexual development and reproductive function. While permanent adrenocortical insufficiency is rare in all species, emerging evidence in both human and equine medicine suggests that transient, reversible adrenocortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 81 publications
4
52
0
1
Order By: Relevance
“…Additional studies are warranted to demonstrate the consistency and elucidate the mechanism of this finding. The finding in this study that ACTH and cortisol concentrations in blood samples from neonatal foals were correlated is consistent with previous reports from human and veterinary medicine . Although this finding is not original, the consistency with previous results lends credence to our findings and substantiates what others have observed.…”
Section: Discussionsupporting
confidence: 93%
“…Additional studies are warranted to demonstrate the consistency and elucidate the mechanism of this finding. The finding in this study that ACTH and cortisol concentrations in blood samples from neonatal foals were correlated is consistent with previous reports from human and veterinary medicine . Although this finding is not original, the consistency with previous results lends credence to our findings and substantiates what others have observed.…”
Section: Discussionsupporting
confidence: 93%
“…However, any such proposed hydrocortisone replacement regimen must be evaluated further before clinical application in sick and septic foals. The limitation of the study about hydrocortisone replacement, as the authors declared, is that it was conducted only in healthy foals and adult horses; consequently, the effects of illness on daily endogenous cortisol production rate and hydrocortisone pharmacokinetics in foals are not known [2]. Also in human neonatology, it was suggested that, in the absence of better data and in keeping the goal of minimizing drug exposure, a reasonable strategy might be to administer a test dose of 1 mg/Kg and observe the patient for response over the next 2-6 hours.…”
Section: Critical Illness-related Corticosteroid Insufficiencymentioning
confidence: 93%
“…In equine neonatology, corticosteroids have been studied to treat conditions such as adrenal insufficiency during septic shock and prematurity [2]. Other conditions that are treated with corticosteroids are acute lung injury or acute respiratory distress syndrome (ALI or ARDS) in foals of few months of age [3] and immune-mediated hemolytic anemia (IMHA), which have been reported in both neonate [4] and older foals [5].…”
Section: Introductionmentioning
confidence: 99%
“…; Hasegawa et al . ; Hart and Barton ). It will be important to clarify what role endocrine disorders may have in the pathogenesis and manifestations of severe anhidrosis.…”
Section: Laboratory Findingsmentioning
confidence: 98%